Iran’s Health Diplomacy In Strengthening Medical Technology Cooperation With Indonesia: A Case Study Of Telerobotic Surgery And Telemedicine Implementation In Indonesia (2021-2023) - Heryana, Ade Irman; Agustina, Davina Shofa Ari (The Indonesian Islamic Studies and International Relations Association (Insiera), 2025)
Iran-Indonesia bilateral relations have reached 75 years, and both countries have been members of the Organization of Islamic Cooperation (OIC) since 1969. Amid the global health crisis since 2019, Iran and Indonesia have cooperated in various fields, including the health sector. In this contemporary era, Iran's health technology is growing. However, Iran is also facing economic sanctions from Western countries, which impacts Iran's relations with Western countries. Thus, considering the health situation in Indonesia, Iran is trying to expand its health technology by cooperating with Indonesia. This research aims to answer the question of how the implementation of Health Diplomacy was conducted by Iran in Indonesia through the Telerobotic Surgery and Telemedicine project in 2021-2023. The author uses Ilona Kickbush's Global Health Diplomacy Theory approach to analyze the research question. This research uses a qualitative approach with descriptive methods and literature study techniques to obtain data from various sources, such as journals, reports, books, media, and official documents. The results showed that Iran's Health Diplomacy was considered adequate, as seen from the implementation of the Telerobotic Surgery and Telemedicine cooperation, which ran smoothly in 2021-2023. The implementation of this cooperation also has a positive impact on the increasingly intense and sustainable Iran-Indonesia relations.